Preferensi Konsumen Terhadap Atribut Produk Sayuran Organik di Kota Bandar Lampung - Sutarni Sutarni; Teguh Budi Trisnanto; Bina Unteawati (Jurnal Penelitian Pertanian Terapan, 2017)
Specific Objectives of this research are: (1) analyze the attributes of organic agricultural products desired by consumers, (2) analyze the consumer preference for organic food product attributes, this research will be carried out in Bandar Lampung Supermarkets. The choice of location is done intentionally (purposive). Samples were taken as many as 30 respondents who consume organic agricultural products. The analytical method used, namely: Conjoint analysis, valuation of non-market value approach; contigensi valuation method (CVM). Research results show (1) A very important factor in the purchase of organic agricultural products is the first factor, namely: certificate of organic products labeled (for organic certification) reached 54.217%, the second factor is the availability or stock of organic products in the Supermarket (17.419%), the third factor is the packaging of organic agricultural products Â (14.237%), and the last factor is the price of agricultural products (14.127), (2) Consumers prefer lower prices on organic products, organic agricultural products labeled (there is organic certificate of agencies or institutions), the availability or many stock of goods , and attractive packaging using sealed plastic and tidy.